Biodistribution, cardiac and neurobehavioral assessments, and neurotransmitter quantification in juvenile rats following oral administration of aluminum oxide nanoparticles. Issue 8 (2nd December 2020) - Mortensen, Ninell P.; Moreno Caffaro, Maria; Patel, Purvi R.; Snyder, Rodney W.; Watson, Scott L.; Aravamudhan, Shyam; Montgomery, Stephanie A.; Lefever, Timothy; Sumner, Susan J.; Fennell, Timothy R.
Abstract: Little is known about the uptake, biodistribution, and biological responses of nanoparticles (NPs) and their toxicity in developing animals. Here, male and female juvenile Sprague–Dawley rats received four consecutive daily doses of 10 mg/kg Al2 O3 NP (diameter: 24 nm [transmission electron microscope], hydrodynamic diameter: 148 nm) or vehicle control (water) by gavage between postnatal days (PNDs) 17–20. Basic neurobehavioral and cardiac assessments were performed on PND 20. Animals were sacrificed on PND 21, and selected tissues were collected, weighed, and processed for histopathology or neurotransmitter analysis. The biodistribution of Al2 O3 NP in tissue sections of the intestine, liver, spleen, kidney, and lymph nodes were evaluated using enhanced dark‐field microscopy (EDM) and hyperspectral imaging (HSI). Liver‐to‐body weight ratio was significantly increased for male pups administered Al2 O3 NP compared with control. HSI suggested that Al2 O3 NP was more abundant in the duodenum and ileum tissue of the female pups compared with the male pups, whereas the abundance of NP was similar for males and females in the other tissues. The abundance of NP was higher in the liver compared with spleen, lymph nodes, and kidney. Homovanillic acid and norepinephrine concentrations in brain were significantly decreased following Al2 O3 NP administration in female and male pups, whereas 5‐hydroxyindoleacetic acid was significantly increased in male pups. EDM/HSI indicates intestinal uptake of Al2 O3 NP following oral administration. Al2 O3 NP altered neurotransmitter/metabolite concentrations in juvenile rats' brain tissues. Together, these data suggest that orally administered Al2 O3 NP interferes with the brain biochemistry in both female and male pups. Abstract : Oral administration of 10 mg/kg Al2 O3 NP between postnatal days (PNDs) 17–20 resulted in increased liver‐to‐bw ratio in male pups, indication of NP uptake, and altered neurotransmitter/metabolite concentrations in the brain tissues in both male and female rats. Together, these results suggest a low level of Al2 O3 NP uptake following oral exposure, which adversely impacts the liver in male pups and interfere with the brain biochemistry in both female and male pups.